S-9-PAHSA ameliorates cognitive decline in a type 2 diabetes mouse model by inhibiting oxidative stress and apoptosis via CAIII modulation - Wang, Xin-Ru; Huang, Shan-Shan; Wang, Meng; Lin, Jin-Hong; Wang, Jian-Tao; Ren, Jiao-Qi; He, Cheng-Feng; Xue, Wen-Jiao; Wang, Yin; Wang, Xue-Chun; Zhang, Yan-Li; Xiao, Ji-Chang; et al. (Frontiers in Molecular Neuroscience, 2025)
PurposeS-palmitic acid-9-hydroxy stearic acid (SP), a newly characterized endogenous lipid with multifaceted biological activities, is poised to shed light on its potential in diabetes-related cognitive disorder (DRCD). This study aims to uncover the effects of SP on DRCD and the underlying mechanisms.MethodsC57BL/6 mice were fed with high-fat diet for 5 months to induce type 2 diabetes mellitus (T2DM). Subsequently, they received bilateral hippocampal injections of adeno-associated virus (AAV) carrying carbonic anhydrase III (CAIII) shRNA or control shRNA. Following one-month treatment with SP or vehicle, cognitive function was assessed using the Morris water maze and Y-maze tests. Oxidative stress and apoptosis were measured by Enzyme-linked Immunosorbent Assay (ELISA), and hippocampal neuronal morphology was examined through HE, Nissl, or NeuN staining. RNA sequencing (RNA seq), cell viability, tetramethylrhodamine ethyl ester (TMRE) staining, and mitoSOX assays were also performed in cultured PC12 cells.ResultsOur findings demonstrated that CAIII played a pivotal role in enhancing cognitive function in T2DM mice by improving spatial memory. SP ameliorated hippocampal injury by CAIII-mediated AMPK/Sirt1/PGC1α pathway, Bcl-2/Bax ratio elevation, and cleaved-Caspase 3 reduction. CAIII participated in various biological processes in the effects of SP on PC12 cells, including cell viability, lactate dehydrogenase (LDH) release, antioxidant enzymes, the maintenance of mitochondrial membrane potential, and the reduction of mitochondrial reactive oxygen species (ROS).ConclusionOur study revealed that CAIII was integral to the effects of SP on DRCD, suggesting its potential as a therapeutic target for DRCD.